32.0k views
1 vote
Please solve this fast.​

Please solve this fast.​-example-1
User Karcsi
by
6.0k points

2 Answers

4 votes

Answer:

- 24 - 70i

Explanation:

Given

(
√(5) - 7i)²

= (
√(5) - 7i)(
√(5) - 7i)

= 5 - 7
√(5) i - 7
√(5) i + 49i² ( note that i² = - 1 )

= 5 - 14
√(5) i - 49

= - 44 - 14
√(5) i

User Shekhar G H
by
5.3k points
3 votes

Answer:

Explanation:

(a - b)² = a² - 2ab + b²


[√(5) - 7i]^(2)= (√(5))^(2) - 2*√(5)*7i + (7i)^(2)\\\\\\= 5 - 14i√(5)+7^(2)*i^(2)]]= 5 -14i√(5) +49 * -1\\\\= 5 -14i√(5) - 49\\\\= -44 - 14i√(5)

User Thomas Sablik
by
6.1k points